Smoothing cooling demand of buildings with PCM thermal batteries - Lee Seung Ho; Liu Ming; Saman Wasim; Bostrom Michel (Renewable Energy and Environmental Sustainability, 2024)
Escalating energy tariffs and peak cooling demands due to climate change along with expanding use of variable renewable energy supply are presenting new challenges and opportunities for air conditioning system operation and control. This research presents the outcome of an investigation into the use of a thermal battery using salt-hydrate phase change material (PCM) in commercial buildings. A 1.2 m3 modular thermal battery using 15 °C melting temperature salt-hydrate PCM has been designed and fabricated. Its cooling performance and feasibility of integration into a chilled water-cooling system of commercial buildings has been comprehensively investigated. This storage unit can accommodate approximately 52 kWh of energy, featuring a rapid heat discharge rate of 32.58 kW during the initial 30 min to effectively address sudden cooling demands. The overall heat discharge rate closely aligns with simulation results, reaching approximately 96% accuracy. This has been achieved through optimisation of the heat exchanger design through mathematical simulation, detailed testing to match various operational scenarios and evaluation of economic and peak load shifting benefits. The results demonstrate the environmental and economic effectiveness of the PCM thermal battery as an independent component in building cooling systems. It provides a timely response to peak cooling demand and improves thermal comfort of the buildings.